Evaluation of Serum Mammaglobin as an Alternative Biomarker in the Diagnosis of Breast Tumors - Fatima, Maira; Sai Baba, Kompella S. S.; Sreedevi, Neelam N. R.; Kumar, Japa P.; Raju, Gottumukkala S.; Uppin, Shantveer G.; Bhaskar, Madrol V.; Khan, Siraj Ahmed; Iyyapu, Krishna M.; Noorjahan, Mohammed (Journal of Laboratory Physicians, 2022)
Introduction Breast cancer is the most common cancer in women in India and accounts for 14% of all cancers in women. Rise in mortality is due to lack of awareness and proper screening. Mammography and presently available serum biomarkers have low sensitivity and specificity. In our quest to identify a better biomarker, we studied mammaglobin (MAM) in patients with breast cancer and benign breast tumors.Aim To evaluate serum mammaglobin in breast cancer patients and compare it with benign breast tumor patients and healthy controls. To compare it with existing biomarkers serum carcinoembryonic antigen (CEA) and cancer antigen 15–3 (CA 15–3). Materials and methods: This is a cross-sectional, case–control study of 77 subjects, of which 27 were breast cancer patients, 20 benign breast tumor patients, and 30 healthy controls. Serum CEA and CA15–3 were estimated by electrochemiluminescence immunoassay (ECLIA) and mammaglobin (MAM) by enzyme-linked immunosorbent assay (ELISA).Results Mammaglobin and CEA levels were elevated in breast cancer patients, followed by benign breast tumors when compared with controls (P < 0.000001). Mammaglobin showed 81.5% sensitivity, 100% specificity, 100% positive predictive value (PPV), and 88.9% negative predictive value (NPV). CEA showed 88.9% sensitivity, 82.5% specificity, 77.4% PPV, and 91.7% NPV. The area under the curve was the highest for MAM (0.892), followed by CEA (0.889) and CA 15–3 (0.555). CA15–3 showed poor diagnostic efficacy. Combined receiver operating characteristic (ROC) curve of the biomarkers MAM and CEA had an AUC of 0.913.Conclusion Mammaglobin proved to be an efficacious biomarker in diagnosing breast cancer.
Keywords: breast cancer; breast tumor; CA 15–3; CEA; MAM; mammaglobin